Brazilian Protocol for Sexually Transmitted infections 2020: approaching sexually active individuals - Araujo, Maria Alix Leite (Rev Soc Bras Med Trop, 2021)
This article aims to present concepts and clinical practices recommended to approach people with active sex life. These concepts are an integral part of the recommendations of the Clinical Protocol and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections (STI), published by the Ministry of Health of Brazil in 2020. The article proposes a comprehensive approach to sexuality for health promotion. It presents significant aspects of the communication process that must develop, without prejudice and judgment, focusing on sexual and reproductive health. It also highlights relevant points about the exercise of sexuality at specific stages of life, recommending assessment of risks and vulnerabilities and screening for STI and condom use. In this way, it is possible to contribute to exercise their sexuality fully, responsibly, and safely.